Examining the Effects of Time to Diagnosis, Income, Symptoms, and Incidental Detection on Overall Survival in Epithelial Ovarian Cancer: Manitoba Ovarian Cancer Outcomes (MOCO) Study Group. Issue 8 (October 2017) - Altman, Alon D.; Lambert, Pascal; Love, Allison J.; Turner, Donna; Lotocki, Robert; Dean, Erin; Popowich, Shaundra; Nachtigal, Mark W.
Abstract : Objective: The primary objectives of this study were to analyze data on time to diagnosis and correlate this with overall survival. We secondarily analyzed the effects of emergency room visits, symptoms, incidental findings, residence, socioeconomic status, and residual disease on overall survival. Methods: This retrospective population-based descriptive cohort study examined all invasive ovarian cancer cases in Manitoba, Canada, between 2004 and 2010. Clinicopathologic, socioeconomic, and outcome data were collected. Analysis was performed with Cox and logistic regression stratified by early and late stage. Results: Six hundred eighty-seven ovarian cancer patients were identified, with a final cohort of 601 patients: 210 with early-stage (1/2) and 391 with late-stage (3/4) disease. No presenting symptoms were associated with survival outcome. Poorer survival was associated with increasing age ( P = 0.0016) and neoadjuvant chemotherapy ( P = 0.0037). Higher income within the urban setting was also associated with a survival advantage ( P = 0.0037), whereas initial presentation to the emergency room ( P = 0.0399) was associated with decreased survival. Finally, for advanced-stage disease, incidental diagnosis had a significantly improved overall survival (hazard ratio, 0.424; 95% confidence interval, 0.27–0.67; P = 0.0003), even when accounting for confounding factors. Time from first presentation to diagnosis was associated with survival ( P = 0.0309). Conclusions: This study found that time to diagnosis did not negatively impact overall survival, although there was an association. Age, morphology, treatment type, residual disease, medical comorbidities, and income were significant prognostic factors. This is the first study to show a survival advantage to incidentally finding an ovarian cancer. Further research is needed on the outcomes of pelvic examination. Abstract : Supplemental digital content is available in the text.